Astrocytes as cellular mediators of cue reactivity in addiction - Kruyer, Anna (Curr Opin Pharmacol, 2020)
Relapse to addictive drug use remains a major medical problem worldwide. In rodents, glutamate release in the nucleus accumbens core triggers reinstated drug seeking in response to stress, and drug-associated cues and contexts. Glutamatergic dysregulation in addiction results in part from long-lasting adaptations in accumbens astroglia, including downregulation of the glutamate transporter GLT-1 and retraction from synapses after withdrawal from psychostimulants and opioids. While their capacity to clear glutamate is disrupted by drug use and withdrawal, accumbens astrocytes undergo rapid, transient plasticity in response to drug-associated cues that reinstate seeking. Cued reinstatement of heroin seeking, for example, restores synaptic proximity of astrocyte processes through ezrin phosphorylation, and enhances GLT-1 surface expression. These adaptations limit drug seeking behavior and largely occur on non-overlapping populations of astroglia. Here we review the growing literature supporting a critical role for accumbens astrocytes in modulating glutamate transmission during drug seeking in rodent models of relapse.